Tantangan dalam Transformasi Pendidikan Kedokteran Gigi pada Era Pandemik COVID-19 - Eko Prastyo; Dylmoon Hidayat; Slamet Harjaya (Jurnal Keperawatan Silampari, 2022)
This study aims to assess the challenges faced by universities providing dental education in the era of the Covid-19 pandemic. This research method uses a narrative review research method. The search results obtained 143 articles and brought five pieces relevant to the focus and purpose of the literature review. The data sources obtained are then extracted using the design, sample, variable, instrument, and analysis (DSVIA) method. In the implementation of dental education in the era of the Covid-19 pandemic, many obstacles were encountered related to the learning curriculum, learning media, online assessment, conducting research and laboratory practicum, and so on. In conclusion, the biggest challenge in dental education is the steps or policies that must be taken to ensure the continuation of dental education activities during the Covid-19 pandemic. Keywords: Covid-19, Learning, Dental Education